Respecting rights? : assessing oil palm companies’ compliance with FPIC obligations : case study: Maryland Oil Palm Plantation in south-eastern Liberia /: assessing oil palm companies’ compliance with FPIC obligations : case study: Maryland Oil Palm Plantation in south-eastern Liberia. (December 2015) - Forest Peoples Programme,; Social Entrepreneurs for Sustainable Development (Organisation),
No abstract available